2021
DOI: 10.3389/fvets.2021.650531
|View full text |Cite
|
Sign up to set email alerts
|

Hepatosplenic Protective Actions of Spirulina platensis and Matcha Green Tea Against Schistosoma mansoni Infection in Mice via Antioxidative and Anti-inflammatory Mechanisms

Abstract: Schistosomiasis, a major parasitic illness, has high morbidity and negative financial effects in subtropical and tropical countries, including Egypt. The present study investigated the therapeutic effects of Spirulina platensis (SP) and matcha green tea (MGT) in Schistosoma mansoni-infected mice combined with tracing their possible antioxidant and anti-inflammatory impacts and their protective potency. A total of 60 Swiss albino mice were randomly allocated into six groups (n = 10): control group (CNT, receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Infection with S. mansoni induces hepatocellular damage and raises circulating levels of the liver enzymes ALT and AST. Furthermore, it inhibits protein production (Ramez et al 2021). After S. mansoni infection, circulation levels of AST and ALT were dramatically elevated, although total protein and globulins were reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection with S. mansoni induces hepatocellular damage and raises circulating levels of the liver enzymes ALT and AST. Furthermore, it inhibits protein production (Ramez et al 2021). After S. mansoni infection, circulation levels of AST and ALT were dramatically elevated, although total protein and globulins were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with S. mansoni induces hepatocellular damage and raises circulating levels of the liver enzymes ALT and AST. Furthermore, it inhibits protein production (Ramez et al 2021 ). After S .…”
Section: Discussionmentioning
confidence: 99%
“…Bin Dajem et al showed that green tea at a concentration of 3% (w/v) reduced hepatocellular necrosis and perivascular collagen fibers by decreasing lipid peroxidation, but failed to significantly improve liver function ( Bin Dajem et al, 2011 ). Another study found Matcha (a Japanese green tea powder made from finely powdered dried tea leaves) to have lower levels of polyphenols and higher levels of caffeine, quercetin, and rutin than traditional green tea ( Ramez et al, 2021 ). Matcha (3 g/kg b. w) contained more theanine and rutin than other green teas, reducing TNF-α, IFN-γ, and IL-13 levels, increasing IL10 levels, which led to the inhibition of the development of liver granulomas, the restoration of SOD, CAT and GSH-Px activity as well as MDA and TAC levels through antioxidant capacity ( Kochman et al, 2020 ).…”
Section: Natural Products Against Schistosomiasis-associated Liver Fi...mentioning
confidence: 99%
“…It is therefore not surprising to mention that there is an urgent need to develop eco-friendly effective alternatives for these chemicals. Interestingly, the use of herbal medications becomes a promising alternative approach for the treatment of various infectious agents because of their biodegradability, target efficiency, and cost-effectiveness, and therefore, they gained a considerable interest in tropical and subtropical regions (18)(19)(20)(21)(22)(23)(24)(25)(26). Among others, plant-derived materials and their bioactive substances were proposed as substitutes for synthetic acaricides due to their activity against ticks (27).…”
Section: Introductionmentioning
confidence: 99%